Sweden : Selected Issues. (IMF Staff Country Reports; Country Report ;, 1998)
This Selected Issues paper on Sweden reviews economic developments in Sweden during 1994-98. In 1994, the general government expenditure-to-GDP ratio stood at 70 percent, up from below 60 percent of GDP in the late 1990s; meanwhile, the revenue ratio was just under 60 percent of GDP, down from about 65 percent of GDP in the late 1980s. On the expenditure side, transfers to households accounted for 37 percent of general government expenditure in 1994, subsidies and other transfers to businesses 10 percent, consumption 39 percent, investment 4 percent, and interest payments 10 percent.